Montmorillonite-based essential oil carrier and its effects on non-target species: an environmental perspective on its risk assessment - Machado, Sofia; Ganilho, Catarina; Andreani, Tatiana; Sousa, Rose Marie O. F.; Ribeiro, Artur; Pereira, Ruth (Frontiers in Toxicology, 2025)
IntroductionEssential oils (EO), rich in bioactive metabolites with biocidal activity, present great potential for agricultural applications as new biopesticides. However, their high volatility and sensitivity to environmental conditions limits their application. To address these limitations, nanotechnology-based formulations have been developed, incorporating EO into natural clays such as montmorillonite (MMT). Due to its colloidal properties, high adsorption capacity, and modifiable surface, MMT serves as an effective carrier for stabilizing EO while controlling their release. Besides aiming to enhance EO efficacy, these MMT-based formulations also aim to minimize EO toxicity to non-target organisms.Materials and methodsIn this study, the toxicity of Satureja montana EO (SM EO), of its dispersant agent Tween 20®, of the MMT nanoclay and of the nanoclay-EO formulation was evaluated using aquatic (Aliivibrio fischeri, Raphidocelis subcapitata, Lemna minor and Daphnia magna), and terrestrial (Folsomia candida and soil microbiota) non-target model organisms, following standard protocols.ResultsAmong the tested species, R. subcapitata and D. magna, exhibited the highest sensitivity, with D. magna showing an EC50 of 0.011 mg mL-1 and a complete growth inhibition being observed for R. subcapitata at concentrations ≥0.021 mg mL-1, for the nanoclay-EO formulation. F. candida reproduction was also significantly reduced for all tested concentrations of the nanoclay-EO formulation. In contrast, it was observed a stimulatory effect on soil microbial activity particularly for dehydrogenase and acid phosphatase enzymes.DiscussionThese findings suggest that the nanoclay-EO formulation did not reduce the toxicity of SM EO, and in some cases, may even raise ecotoxicological concerns, particularly for aquatic and soil invertebrates. This study highlights the importance of detailed ecotoxicological evaluations of biopesticide formulations based on plant-based and materials as essential oils, and other natural materials, as they cannot be assumed as safe compounds. To the best of our knowledge ecotoxicological data is limited for most of the EO including some that already in the market. Based on these results, the concentrations to be tested for efficacy against target organism (safe to non-target organism) should be lower than 0.007 mg mL-1.